Penelitian Islam: Dasar dan Filosofi - Marzuki, Abu Bakar (IAIN Palangka Raya, 2016)
This article is a continued understanding of some thoughts delivered by the Islamic study experts. Actually, Islamic study orientation is still floating and it does not have a clear goal. Some parts of Islamic study is